There Is No Brain: Rethinking Neuroscience through a Nomadic Ontology. (June 2019) - Gruber, David R
Building from recent attempts in the humanities and social sciences to conceive of creative, entangled ways of doing interdisciplinary work, I turn to Braidotti's 'nomadic ontology' to (re)vision the human body without a brain. Her exploration of the body as a 'threshold of transformations' is put into conversation with Deleuze's comments on neurobiology to consider what a brainless body might do, or undo, in neuroscientific practice. I ground discussion in a case study, detailing the practices of brain decoding or 'mind reading, ' re-interpreting Rose's account. Therein, I argue that the technical-social configurations of brain decoding are unlikely to usher in a radically new ontology, as Rose suggests. To better match Rose's vision and align with new ontologies in cultural theory, I argue that neuroscience must become nomadic and embrace a body without a brain. I then conclude with six recommendations towards a nomadic neuroscience.